PENGARUH MODEL PEMBELAJARAN THINK PAIRE SHARE DISERTAI MIND MAP TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN KREATIVITAS SISWA KELAS X SMA PADA MATERI EKOSISTEM. SKRIPSI. UNIVERSITAS MAHAPUTRA MUHAMMAD YAMIN. SOLOK. - Elsi Febriani; Helvita Roza; Ratih Komala Dewi; Darmanella Dian Eka Wati; Chairul Amri; Afrahamiryano; Irwan Hanafi (LPPM Universitas Ekasakti, 2024)
The purpose of this study is to determine whether the think pair share and mind map learning models have an influence on students' critical thinking skills in class X SMA, as well as their relationship with their creativity with ecosystem material. This study used a quasy experiment with a one group pretest-posttest design. Students of SMAN 1 Payung Sekaki formed the population. The number of students used was 25 people. In data collection, mean difference test technique (t-test) was used. The pre-test result was 68.20 rising to 85.20, and the paired t-test result was 9.106 rising to 1.697, with a probability value below 0.05 (0.000 <0.05). This shows that the Think Pair Share and Mind Map learning models have an impact on critical and creative thinking skills in Class X SMA on ecosystem material. Thus, it can be concluded that students in Class XE2 of SMAN 1 Payung Sekaki showed improvement in their critical thinking ability and creativity related to ecosystem material.